Sumoylation of Influenza A Virus Nucleoprotein Is Essential for Intracellular Trafficking and Virus Growth - Han, Qinglin (American Society for Microbiology, 2014)
Viruses take advantage of host posttranslational modifications for their own benefit. It was recently reported that influenza A virus proteins interact extensively with the host sumoylation system. Thereby, several viral proteins, including NS1 and M1, are sumoylated to facilitate viral replication. However, to what extent sumoylation is exploited by influenza A virus is not fully understood. In this study, we found that influenza A virus nucleoprotein (NP) is a bona fide target of sumoylation in both NP-transfected cells and virus-infected cells. We further found that NP is sumoylated at the two most N-terminal residues, lysines 4 and 7, and that sumoylation at lysine 7 of NP is highly conserved across different influenza A virus subtypes and strains, including the recently emerged human H7N9 virus. While NP stability and polymerase activity are little affected by sumoylation, the NP sumoylation-defective WSN-NP(K4,7R) virus exhibited early cytoplasmic localization of NP. The growth of the WSN-NP(K4,7R) virus was highly attenuated compared to that of the wild-type WSN virus, and the lysine residue at position 7 is indispensable for the virus's survival, as illustrated by the rapid emergence of revertant viruses. Thus, sumoylation of influenza A virus NP is essential for intracellular trafficking of NP and for virus growth, illustrating sumoylation as a crucial strategy extensively exploited by influenza A virus for survival in its host. IMPORTANCE Host posttranslational modifications are heavily targeted by viruses for their own benefit. We and others previously reported that influenza A virus interacts extensively with the host sumoylation system. However, the functional outcomes of viral sumoylation are not fully understood. Here we found that influenza A virus nucleoprotein (NP), an essential component for virus replication, is a new target of SUMO. This is the first study to find that NP from different influenza A viruses, including recently emerged H7N9, is sumoylated at conserved lysine 7. Our data further illustrated that sumoylation of influenza A virus NP is essential for intracellular trafficking of NP and virus growth, indicating that influenza A virus relies deeply on sumoylation to survive in host cells. Strategies to downregulate viral sumoylation could thus be a potential antiviral treatment.